Advanced electrical installation work - Linsley, Trevor (New York, NY : Routledge, 2013)
'Aligned with the 17th edition IET Wiring Regulations, this new edition has been fully updated to cover the new City & Guilds 2365 course. Written in an easy to follow style with each chapter of the book dedicated to a unit of the syllabus, this book helps students to master each topic before moving on to the next. End of chapter revision questions help students to check their understanding and consolidate key concepts learnt in each chapter. Online material also helps students to practice and revise their skills, making this a textbook that no electrical installations student should be without.'--
'Aligned with the 17th edition IET Wiring Regulations, this new edition has been fully updated to cover the new City & Guilds 2365 course. Written in an easy to follow style with each chapter of the book dedicated to a unit of the syllabus, this book helps students to master each topic before moving on to the next. End of chapter revision questions help students to check their understanding and consolidate key concepts learnt in each chapter. Online material also helps students to practice and revise their skills, making this a textbook that no electrical installations student should be without'--
Includes index.
'Level 3' -- on cover.
Keywords: Electric apparatus and appliances -- Installation; Electric machinery -- Installation; Electric wiring, Interior